Evolution of volatile compounds during the development of Muscat grape ‘Shine Muscat’ (Vitis labrusca × V. vinifera) - Wu, Yusen; Zhang, Wenwen; Song, Shiren; Xu, Wenping; Zhang, Caixi; Ma, Chao; Wang, Lei; Wang, Shiping (Food chemistry, 2020)
[Display omitted] •Qualitative and quantitative representative volatiles in Shine Muscat were found.•Terpenes concentrations decrease sharply due to dilution effect at pre-softening.•LOX, ADH and substrate alcohols are the limiting factors of LOX pathway.•Developmental patterns of volatiles in grape of all aroma types were summarized. This study investigated the evolution of both free and bound volatile compounds in ‘Shine Muscat’ grape from post-fruit set to post-maturity and limiting factors of the lipoxygenase (LOX) pathway. C6 compounds and terpenes were the main free and bound volatile compounds, respectively. At pre-softening, volatile compounds concentrations were mainly regulated by expansion dilution, and terpene concentrations decreased significantly, which resulted in the minimum terpene concentrations occurred at softening. The volatile compounds were mainly regulated by metabolic synthesis at post-softening, and the production of C6 compounds, terpenes and esters largely began at 10, 12 weeks post-flowering and maturity stages, respectively. In the LOX pathway, LOX, alcohol dehydrogenase and the substrate alcohols were the limiting factors. The aroma maturity stages occurred at 15.4 weeks post-flowering. Finally, the developmental patterns of the volatile compounds in grape were summarized considering previous results in neutral and non-Muscat aromatic varieties.